Gut microbiota and autism - Boreński, Grzegorz; Wójcik, Magdalena; Poleszak, Julita; Szabat, Przemysław; Szabat, Marta; Milanowska, Joanna (Journal of Education, Health and Sport, 2019)
Introduction: Autism spectrum disorders (ASD) constitutes a group of brain developmental disorders and is characterized by difficulty with social communication and restricted, repetitive patterns of behavior, interest, or activities. ASD has no clear etiology and research is still ongoing to find it. Gut microbiota seems to have significant impact on the development of autism. The aim of the study: The purpose of this systemic review was to collect and analyse available data about the role of gut microbiota and new methods of treatment of ASD. Material and method: Standard criteria were used to review the literature data. The search of articles in the PubMed and Google Scholar database was carried out using the following keywords: autism spectrum disorder, gut microbiota, probiotics. Description of the state of knowledge: In the studies we can found that symptoms from gastrointestinal tract occur more often in patients with ASD. Many studies confirm alterations in gut microbiota accompanying autism. The general changes are imbalance between Bacteroidetes and Firmicutes phyla, increased population of Sutterella and higher level of cultured Clostridium species in the feces. Researchers try to find a reason of these microbiota changes and the main cause they indicate is using antibiotics. Restoration of microbial balance in the colon, for instance by probiotics or microbiota transfer therapy may have beneficial effect on treatment of ASD. Summary: Complicated relationship between gut microbiota and brain needs more studies, but at that point we can find its association with autism and ASD and also with anorexia nervosa, depression and other mood disorders and GI diseases. Among currently available methods of treatment we can distinguish behavioural treatment, pharmacological approach (risperidone and aripiprazole) and complementary and alternative medicine therapies. Understanding the impact of microbiota on autism opens up new paths of treatment, for instance probiotics, fecal microbiota transplantation or microbiota transfer therapy. Although, there is a great need for more researches of their efficacy.